Interface of Human Intelligence and Artificial Intelligence: Possibilities and Challenges for the Indian Legal Educational Framework (Journal of Informatics Education and Research, 2026)
The recently started integration of artificial intelligence (AI) into educational systems across the globe, including India, has created revolutionary opportunities coupled with associated challenges. The opportunities may include increased access to educational resources, personalized learning platforms, innovative pedagogical tools, enhanced research capabilities, predictive analysis for dispute resolutions, etc. The associated challenges may include threat to academic integrity, erosion of critical reasoning affecting human capabilities of critical thinking, algorithmic biases benefiting a specific class of society, lack of ethical and moral accountability, regulatory gaps affecting quality education, infrastructural disparities, etc. The research paper examines possibilities of integration of human intelligence and artificial intelligence in the existing Indian legal educational framework to ensure more opportunities and with minimum challenges impacting its quality, accessibility and efficacy. The paper analyzes the challenges of digital divides, pedagogical challenges and faculty readiness with the help of case studies from National Law Universities and other higher educational institutions. Using doctrinal analysis, the paper has also included study of the regulatory framework of the Bar Council of India, the judicial approach as to use of artificial intelligence in legal field. The paper recommends for curriculum reforms, ethical trainings based on written guidelines and regular policy interventions to make this integration more human centric and ethically regulated educational framework.